(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Albadawi I. Keywords: scientific journal, the Institute, publications, themes, problems, Arab world, Arab countries, ‘Arab Spring’. This article analyzes the coverage of events and issues of the Arab East in scientific journals of the Russian Academy of Sciences: ‘World Economy and International Relations’, ‘Orient’, ‘Asia and Africa today’, issued in 2012. This theme is of great interest because of the events that rapidly swept over Tunisia, Yemen, Egypt, Libya, and Syria and had tragic consequences considerably influencing international relations and world politics. Scientific journals in their publications have tried to understand the reasons and consequences of the ongoing socio-political transformations in that region. The article presents the opinions of well-known experts and public figures such as: research associates of Institute of Africa and Institute of Oriental studies of the Russian Academy of Sciences, foreign experts. political scientists, international observers.